2018
DOI: 10.1186/s12891-018-2099-2
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and early revision rate after medial unicompartmental knee arthroplasty: prospective results from a non-designer single surgeon

Abstract: BackgroundThis prospective study evaluates outcomes and reoperation rates for unicompartmental knee arthroplasty (UKA) from a single non-designer surgeon using relatively extended criteria of degenerative changes of grade 2 or above in either or both non-operated compartments.Methods187 consecutive medial mobile bearing UKA implants were included after history, clinical assessment and radiological evaluation. 91 patients had extended clinical outcomes. Post-operative assessment included functional scoring with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Only Chan et al's study [9] found a higher number of distal deep vein thrombosis cases in bilaterally operated upon patients, but they did not benefit from postoperative drug thromboprophylaxis. No infectious complications were found in our study, which is also consistent with the literature [26,27].…”
Section: Discussionsupporting
confidence: 93%
“…Only Chan et al's study [9] found a higher number of distal deep vein thrombosis cases in bilaterally operated upon patients, but they did not benefit from postoperative drug thromboprophylaxis. No infectious complications were found in our study, which is also consistent with the literature [26,27].…”
Section: Discussionsupporting
confidence: 93%
“…Also, in other studies, osteoarthritis in the lateral joint compartment is the most common reason for the revision in MB-UKA [ 17 ]. An important implant-specific reason for revision is the mobile polyethylene inlay, which shows a 0.6%-3.4% dislocation risk [ 3 , 6 , 8 , 11 , [18] , [19] , [20] , [21] , [22] , [23] ].…”
Section: Discussionmentioning
confidence: 99%
“…This has led to recommendations such as a 'minimum' surgeon UKA usage of 20% and an 'optimum' usage of 40-60% to minimize the risk of revision [19]. This increase in usage is supported by studies reporting similar clinical outcomes when using 'extended' UKA indications [8], accepting higher grade patellofemoral chondral change [13], or ignoring BMI [21].…”
Section: Introductionmentioning
confidence: 99%